Stability of Composite Cylindrical Shells with Nonclassical Hygrothermal-Electro-Elastic Coupled Loads - Ni, Yiwen; Zhu, Shengbo; Tong, Zhenzhen; Xu, Xinsheng; Zhou, Zhenhuan; Lim, C. W.; Wadee, Ahmer M.; Yiatros, Stylianos (My University, 2023)
An accurate nonlinear hygrothermal-electro-elastic (HTEE) buckling analysis of piezoelectric fiber-reinforced composite cylindrical shells subjected to the coupled loading effects of axial compression and hydrostatic pressure was established by considering the nonuniform prebuckling effect. Nonlinear governing equations were derived based on higher-order shear deformation theory and Novozhilov's nonlinear shell theory. Accurate critical buckling stresses and pressures and explicit buckling modes for both axisymmetric and nonaxisymmetric buckling were obtained by the Galerkin method. A comparison between the new prediction and existing results is presented and excellent agreement is reported. A comprehensive parametric study of geometric parameters, end conditions, distribution patterns, and hygrothermal-electric multiphysical fields on the buckling behavior of HTEE composite cylindrical shell is also analyzed and discussed.